The Charge Storage Mechanism and Durable Operation in Olivine–Lithium–Iron–Phosphate for Mn‐based Hybrid Batteries - Jangwook Pyun; Hyungjin Lee; Hyeonjun Lee; Sangki Lee; Seunghyeop Baek; Hyeju Kwon; Seung‐Tae Hong; Munseok S. Chae (Advanced Science)
Abstract Aqueous batteries have garnered considerable attention because of their cost‐effectiveness, sufficient capacity, and non‐flammable water‐based electrolytes. Among these, manganese batteries are particularly attractive owing to their stability, abundance, affordability, and higher energy density. With a lower redox potential (Mn: −1.19 V vs SHE) than zinc (Zn: −0.76 V vs SHE), manganese batteries theoretically offer superior energy density over traditional zinc‐based systems. In this study, LiFePO4 is introduced as a cathode material in aqueous manganese‐based hybrid batteries for the first time. Through electrochemical characterization and advanced structural and spectroscopic analyses, the charge storage mechanisms of protons in to the FePO4 are elucidated. Cation diffusion pathways are also investigated via diffusion barrier calculations. This study presents manganese hybrid batteries with a good stability and capacity of ≈109.2 mAh g−1 at 40 mA g−1, alongside a cycle retention of 42.1% after 3000 cycles at 320 mA g−1. Furthermore, an Mn2+/Li+ hybrid battery, achieving ≈1.6 V and superior durability (81.5% @ 1000th), is proposed.